Acute Treatment With Fingolimod Does Not Confer Long-Term Benefit in a Mouse Model of Intracerebral Haemorrhage - Diaz Diaz, Andrea C.; Shearer, Jennifer A.; Malone, Kyle; Waeber, Christian (Frontiers in Pharmacology, 2021)
Intracerebral haemorrhage (ICH) has no specific treatment, but accounts for up to 15% of all strokes and has the highest mortality. Fingolimod (FTY720) is an immunomodulator approved for the management of multiple sclerosis, with abundant evidence of efficacy in experimental ischemic stroke, and more limited evidence in experimental ICH. The goal of this study was to confirm the efficacy of fingolimod in experimental ICH using rigorous and statistically well-powered studies. ICH was induced in C57BL/6JOlaHsd male and female mice by intrastriatal bacterial collagenase injection. Fingolimod (0.5 mg/kg) or saline was administered intraperitoneally after 0.5, 24 and 72 hours, in a randomized and blinded manner. Functional improvement with cylinder, wire hanging, and foot fault tests was evaluated one and two weeks later. Lesion volume and hemispheric atrophy were quantified at the 14-day endpoint. There was a higher mortality in saline-treated females compared to fingolimod-treated females and saline-treated males. There was no treatment- or gender-related difference in the behavioural tests. Histological outcome measures did not differ between any of the groups. These results, contrasting with those of previous studies of fingolimod in experimental ICH, emphasize the importance of rigorous testing of this agent in models more representative of the clinical situation.